Validation of Leaf Area Estimation Models (UZCELIK-I) Evaluated for Some Horticultural Plants - Çelik, Hüseyin; Uzun, S. (My University, 2002)
In this study, avocado, Lotus plum, selected persimmon (52 UN 13), Hayward kiwifruit, aubergine, pepper, cucumber, Black grape (Vitis labrusca L.), Narince (Vitis vinifera L.), red-currant, summer squash, runner bean, Heritage red raspberry and Chester blackberry plant species were used to validate the regression equations of UZCELIK-I. The actual leaf area of the plants were measured by PLACOM Digital Planimeter and predicted leaf area by using UZCELIK-I equations based on widest lamina width and length of leaves. The equations were validated using the residual values between predicted and measured leaf areas. R2 values for the relations between actual and predicted leal areas of the tested species were found to be 0.972, 0.918, 0.983, 0.971, 0.949, 0.988, 0.966, 0.846, 0.953, 0.953, 0.943, 0.950, 0.950 and 0.925 for avocado, Lotus plum, selected persimmon (52 UN 13), Hayward kiwifruit, aubergine, pepper, cucumber, Black grape (Vitis labrusca L.), Narince (Vitis vinifera L.), red-currant, summer squash, runner bean, Heritage red raspberry and Chester blackberry, respectively.